2023
DOI: 10.3390/ani13172758
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Herd, Calf, and Colostrum Management Practices on Austrian Dairy Farms Using a Scoring System

Nicole Hechenberger,
Katharina Lichtmannsperger,
Daniela Klein-Jöbstl
et al.

Abstract: The objectives of the study were to describe colostrum management on Austrian dairy farms and to explore differences between regions (alpine/flatlands), organic and conventional producing farms, and full-time or part-time operated farms. An online survey (24 questions) on general farm characteristics and herd and calf management was sent to 16,246 farmers. In total, 2328 farmers (response rate 14.3%) answered the questionnaire. To allow an objective comparison, a scoring system was implemented. Farm size is, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Seven farms already participated actively in a previous project by the Austrian Animal Health Service on the evaluation of colostrum management in dairy farms. A part of this larger investigation has been published previously [ 14 ]. The remaining 4 farms joined the study on their own intention as they could provide additional samples conveniently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven farms already participated actively in a previous project by the Austrian Animal Health Service on the evaluation of colostrum management in dairy farms. A part of this larger investigation has been published previously [ 14 ]. The remaining 4 farms joined the study on their own intention as they could provide additional samples conveniently.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the probability of a low serum immunoglobulin concentration in calves increases significantly (odds ratio = 10.7), if the colostrum contains less than 50 g/L IgG [ 13 ]. Preliminary results from a project by the Austrian Animal Health Service on the evaluation of colostrum management on dairy farms show that 49.8% of the investigated colostrum samples showed Brix values of less than 22% [ 14 ]. Besides high colostrum quality the time between parturition and colostrum delivery to the neonatal calf plays an essential role, since the absorption of immunoglobulins in the intestine decreases within the first 24 h of life and completely ceases at 24 to 36 h. In summary, timing of colostrum feeding after parturition (within 2 h), colostrum quality (≥ 50 g/L IgG) and the amount of colostrum fed to the calf (> 4 L) within the first hours of life are the most important factors to prevent FTPI [ 1 , 3 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%